2021
DOI: 10.1007/s10734-021-00748-x
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese higher education students’ adaptation to online teaching and learning in times of the COVID-19 pandemic: personal and contextual factors

Abstract: The COVID-19 pandemic brought about a global crisis affecting all sectors of society. Higher education is no exception. The closure of higher education institutions has dictated a sudden and unexpected transition from face-to-face to remote teaching to mitigate the spread of the SARS-CoV-2. This paper draws upon a wider piece of research which aimed to understand how higher education students adapted to the closure of their institution and how they looked at their experience of online teaching and learning. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 49 publications
(56 reference statements)
8
86
1
4
Order By: Relevance
“…Additionally, noncognitive factors could interfere with true scores since studies have shown differences in stress levels, anxiety, and feelings about online learning and assessment among those who have different levels of experience with online learning (Flores et al, 2021;Pesha & Kamarova, 2020). Those with more experience and who were previously enrolled in online instruction had an easier transition during the pandemic.…”
Section: Equity and Fairness Concerns With Online Assessmentmentioning
confidence: 99%
“…Additionally, noncognitive factors could interfere with true scores since studies have shown differences in stress levels, anxiety, and feelings about online learning and assessment among those who have different levels of experience with online learning (Flores et al, 2021;Pesha & Kamarova, 2020). Those with more experience and who were previously enrolled in online instruction had an easier transition during the pandemic.…”
Section: Equity and Fairness Concerns With Online Assessmentmentioning
confidence: 99%
“…A vast number of studies around the globe have considered the emerging educational challenges posed by the COVID-19 pandemic. Even considering the Portuguese reality, several studies have already been produced [9,[14][15][16][17][18][19][20]. However, those studies have focused mainly on the perspective of teachers and schools, which, albeit fundamental, leaves out the fundamental role played by the other denominator in this complex equation: students and parents' perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic caused by SARS-CoV2 forced most sectors to go through a process of adaptation to emerging situations in a context that generated uncertainty ( Flores et al, 2021 ). The emergency situation inevitably affected the education sector and those involved in the learning/teaching process ( Joshi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%